Analisis Faktor-Faktor Yang Mempengaruhi Pembiayaan Bermasalah Pada Bank Syariah Di Indonesia Dengan Pendekatan Error Correction Model - Mohammad Dendi Abdul Nasir; Nunuk Khomariyah (Universitas Muhammadiyah Surabaya, 2021)
Banking plays a very important role in the country's economy. Financing of Islamic Banking certainly has non-performing financing. Worsening the NPF ratio means Syariah Bank has high level of financial problems. This research aims to analyze the influence of internal factors (asset and financing deposit ratio) and external factors (inflation and exchange) against NPF to Syariah Bank in Indonesia. This research used a secondary data sourced from Indonesian Bank in Januari 2011 to June 2018. With using Error Correction Model (ECM) this research's result shows that in the short term only FDR variable that has a significant impact on the NPF, while asset variable, inflation and exchange aren't influential. Then in the long term, asset variable and inflation influence significantly against Syariah Bank NPF, Whereas FDR variable and exchange aren't influential.Keywords: Asset, excange, FDR, inflasi and NPF